Practical Aspects of Using the Creations of Young Uzbek Composers in General Education Schools (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, the practical aspects of using the works of young Uzbek composers in general education schools, the implementation of the goals and tasks of music education are directly related to music lessons at school, the concept of music education includes music science at school along with other subjects. particular importance is given in detail.